A Randomized Control Trial to Determine the Need for Postoperative Antibiotics after Laparoscopic Appendicectomy in Nonperforated Appendicitis - Azizullah Khan Sherani, Bezan Baloch, Saleem Javed, Mehmood Ali, Saiqa Rafiq, Abdullah Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute appendicitis is the most common cause of acute abdominal pain. Postoperative surgical site infections (SSIs) can be avoided with the proper administration of prophylactic antibiotics. Nevertheless, there is no definitive recommendation about the length of time that antibiotics should be used. A sole preoperative preventive dosage has been commended by a number of random trials. Objective: The research goal was to study the postoperative use of antibiotics afterwards laparoscopic appendectomy for appendicitis of nonperforated nature. Methods: This study was carried out at the Surgery Department, BMC/Bolan Medical Complex Hospital Quetta for a period of six months from October 2022 to March 2023. Two groups of 150 patients with nonperforated appendicitis received laparoscopic appendiciectomy. One preoperative antibiotic therapy was given to 75 patients in group A, while three postoperative antibiotic doses were given to 75 patients in group B. Along with other procedures including abdominal ultrasonography, standard tests like serum creatinine, blood urea, and total blood count were performed. The surgical site from the laparoscopic appendectomy was inspected 48, 72, and 7 hours later to examine the signs of SSI subsequently the operative procedure. To evaluate the gathered data, SPSS 24 was utilized. Fisher's exact test was used to compare infection rates, the chi-square test was used to compare demographic data, and the unpaired t-test was used to assess the mean length of hospital stay. Results: The mean age of group B was 31.82±9.56 years (p=0.621), whereas the mean age of group A was 31.14±10.69 years. Every research participant had discomfort in the right iliac fossa. SSIs of grade III were treated conventionally in four patients (6%) and three patients (4%), respectively, in group A and B. Statistically, there was no difference in the incidence of SSIs between the two groups (p=1.000). Conclusions: This study concluded that a single dose of metronidazole and cefotaxime prior to surgery can decrease the chances of SSIs after surgery. Keywords: Nonperforated appendicitis, Surgical site infection, Laparoscopic appendicectomy